2022
DOI: 10.31234/osf.io/9t3wf
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Prosociality Paradox: How Miscalibrated Social Cognition Creates a Misplaced Barrier to Prosocial Action

Abstract: Behaving prosocially can increase wellbeing among both those performing a prosocial act as well as those receiving it, and yet people may experience some reluctance to engage in direct prosocial actions. We review emerging evidence suggesting that miscalibrated social cognition may create a psychological barrier that keeps people from behaving as prosocially as would be optimal for both their own and others’ wellbeing. Across a variety of interpersonal behaviors, those performing prosocial actions tend to un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…Specifically, letter writer's expectations of their recipient's experience were significantly miscalibrated such that they significantly underestimated how surprised recipients would be to receive the letter, underestimated how surprised they would be about its content, underestimated how positive recipients would feel, and overestimated how awkward receiving a gratitude letter would feel. This general pattern has now been replicated in all 17 subsequent iterations of this learning exercise that we have conducted so far at the time of this writing (Epley, Kumar, et al, in press), demonstrating a very robust effect. An additional experiment conducted by Kumar and Epley (2018) confirmed that people's expectations of a recipient's response are related to their interest in expressing their gratitude to a given recipient, suggesting that miscalibrated expectations might keep people from expressing appreciation as often as they truly feel it, missing opportunities to increase both their own and others' wellbeing through this prosocial act.…”
Section: Undervaluing Appreciationsupporting
confidence: 55%
“…Specifically, letter writer's expectations of their recipient's experience were significantly miscalibrated such that they significantly underestimated how surprised recipients would be to receive the letter, underestimated how surprised they would be about its content, underestimated how positive recipients would feel, and overestimated how awkward receiving a gratitude letter would feel. This general pattern has now been replicated in all 17 subsequent iterations of this learning exercise that we have conducted so far at the time of this writing (Epley, Kumar, et al, in press), demonstrating a very robust effect. An additional experiment conducted by Kumar and Epley (2018) confirmed that people's expectations of a recipient's response are related to their interest in expressing their gratitude to a given recipient, suggesting that miscalibrated expectations might keep people from expressing appreciation as often as they truly feel it, missing opportunities to increase both their own and others' wellbeing through this prosocial act.…”
Section: Undervaluing Appreciationsupporting
confidence: 55%
“…Fraud can be perpetrated by people from different educational and social backgrounds and different levels of an organisation (Epley and Kumar, 2019). As mentioned previously, one of the best possible approaches that can be implemented by an organisation is an increase in fraud awareness for all staff levels, regardless of their position.…”
Section: Research Results and Analysismentioning
confidence: 99%
“…In this point, levels of employee morale or loyalty can be reflective of the core values of a company. Creating an ethical culture thus requires thinking about ethics not simply as a belief problem but also as a design problem (Epley and Kumar, 2019).…”
Section: Research Results and Analysismentioning
confidence: 99%
“…A compliment can certainly be insincere, as Silver and Small (2023) point out, but existing research has not examined how variance in a prosocial actor's intentions might affect a recipient's experience. For instance, participants in our research on expressions of gratitude (Kumar & Epley, 2018; see also Epley et al, in press) wrote genuine letters to people they felt a deep appreciation towards. These expressions were therefore very sincere and thoughtful.…”
Section: Intentions: Self‐care or Other‐care?mentioning
confidence: 96%